Transformation Typology of Arabic Meanings - Muhandis Azzuhri; Muslich Shabir; Athoillah Islamy (Arabic Education Program IAIN Pekalongan, 2021)
This research aims to reveal the typology of transformation of the Arabic meanings to the sex-related language in the á¸¥adiá¹¡. This library research utilizes contextual semantic theory with linguistic and historical approaches. The results show that several factors influenced the transformation of the meaning of sex-related language in the á¸¥adiá¹¡s. The first is social and cultural contexts. There were several sexual behaviors in the prophetic era that were considered deviant (sexual deviation) because they were not in accordance with Arab social culture at that time. The second is emotive and psychological context by refining a word Ù†ÙŠÙƒ / intercourse which later was translated into Ø¨ÙØ¶Ù’Ø¹Ù/goods, ÙŠÙØ¶Ù‰/ irrigating and ÙŠÙ„Ù…Ø³ / touching. The third is linguistic context. It is not idiomatic, such as a word Ø®Ø§ØªÙ… / sealing, which can change the compilation meaning when the word is structured with other words as in the á¸¥adiá¹¡ Ù„Ø§ ØªÙØªØ Ø§Ù„Ø®Ø§ØªÙ… Ø¥Ù„Ø§ Ø¨ØÙ‚Ù‡. The word is a metaphor meaning of the 'virginity' term. The fourth is the context of situations and conditions. This context explains that the â€˜sex termâ€™ can transform in meaning because it was conveyed in different situations and conditions with the euphemism and kinÄyah (metaphor) expressions, such as ÙŠØ¬Ø¨ÙˆÙ†, Ø§Ù„ØºÙŠÙ„Ø© and ØÙˆÙ„Øª Ø±ØÙ„ÙŠ Ø§Ù„Ø¨Ø§Ø±ØØ©.